Combined effects of exonic polymorphisms in CRHR1 and AVPR1B genes in a case/control study for panic disorder - Keck, Martin E.; Kern, Nikola; Erhardt, Angelika; Unschuld, Paul G.; Ising, Marcus; Salyakina, Daria; Müller, Marianne B.; Knorr, Carolin C.; Lieb, Roselind; Hohoff, Christa; Krakowitzky, Petra; Maier, Wolfgang; et al. (American journal of medical genetics. Part B, Neuropsychiatric genetics, 2008)
Accumulating evidence from animal studies suggests that the corticotropin releasing hormone (CRH) and arginine vasopressin (AVP) neuropeptide systems, contribute to anxiety behavior. To investigate whether polymorphisms in the genes regulating these two systems may alter susceptibility to anxiety disorders in humans, we genotyped 71 single nucleotide polymorphisms (SNPs) in CRH, CRHR1, CRHR2, AVP, AVPR1A, AVPR1B in a German sample from Munich with patients suffering from panic disorder and matched healthy controls (n = 186/n = 299). Significant associations were then replicated in a second German sample with 173 patients with panic disorder and 495 controls. In both samples separately and the combined sample, SNPs within CHRH1 and AVPR1B were nominally associated with panic disorder. We then tested two locus multiplicative and interaction effects of polymorphisms of these two genes on panic disorder. Fifteen SNP pairs showed significant multiplicative effects in both samples. The SNP pair with the most significant association in the combined sample (P = 0.00057), which withstood correction for multiple testing, was rs878886 in CRHR1 and rs28632197 in AVPR1B. Both SNPs are of potential functional relevance as rs878886 is located in the 3′ untranslated region of the CRHR1 and rs28632197 leads to an arginine to histidine amino acid exchange at position 364 of AVPR1B which is located in the intracellular C‐terminal domain of the receptor. These data suggest that polymorphisms in the AVPR1B and the CRHR1 genes alter the susceptibility to panic disorder. © 2008 Wiley‐Liss, Inc.